Analisis Implementasi Program Perawatan Metode Kanguru (PMK) Dan Partisipasi Pasien Pada Pelayanan Kesehatan Bayi Berat Lahir Rendah (BBLR) (Studi pada Pasien di Rumah Sakit Mardi Rahayu Kudus) - Nur Sri Atik; Sri Achadi Nugraheni; Kusyogo Cahyo (Jurnal Manajemen Kesehatan Indonesia, 2016)
Kangaroo Mother Care (KMC) varies in each hospital. This condition can be viewed from the aspects of types of services, competency of human resource, facilities, and means. Implementation is a crucial step in the process of policy. Readiness and participation of parents will support the success of the KMC implementation. A role of family such as attitude, behaviour, and family participation is as a desire to protect a family member who is sick. This research aimed to identify the implementation process of factors of communication, disposition/attitude, resource, bureaucratic structure, and participation of patients and their families in KMC at Mardi Rahayu Hospital. This was qualitative research using in-depth interview and direct observation. Main informants encompassed 4 mothers who had Low Birth Weight (LBW) Babies. Meanwhile, informants for triangulation purpose encompassed 3 trained midwives, 3 trained nurses, and 3 trained paediatricians, nursing manager, and director of medical services. Furthermore, data were analyzed using thematic analysis in which data as the result of in-depth interview were analyzed in accordance with a theme. The implementation of KMC had not been done optimally. Regarding communication, there was no socialization of the program. Therefore, information of the KMC program was unclear, inconsistent. Regarding attitude/disposition of the program implementer, there was not only lack of support from all implementers in implementing the program but also lack of commitment. Regarding resource, there was lack of trained health workers, lack of facilities, and no sustainable fund for the program. Regarding bureaucratic structure, Standard Operating Procedure was needed to be revised and no clear job-sharing in KMC. Mothers had not participated in making decision, implementing, taking benefits, and evaluating yet. This was due to lack of information. As suggestions, the hospital needs to improve socialization of the program, provide implementation guidelines, and implement KMC followed by monitoring and supervising. In addition, the hospital needs to improve communication, information, education (CIE) for mother/family and provide opportunity for clients to implement KMC at the hospital before going home.